Pengaruh Kualitas Pelayanan Dan Lokasi Terhadap Kepuasan Nasabah: Survey pada nasabah salah satu Bank Swasta di Kota Bandung - Febtryanti Yanelka; Imam Heryanto; Ashila Dwiyanisa; Imelda Megawati (Acman: Accounting and Management Journal, 2022)
Customer satisfaction is one of the critical aspects of achieving service goals in marketing. This study aims to determine service quality and location on customer satisfaction. Researchers surveyed one of the private banks in Bandung with several respondents as many as 100 customers. The researchers used path analysis techniques to determine the magnitude of the influence of service quality and location on customer satisfaction. The study results indicate that there is a significant effect of service quality and location on customer satisfaction. Furthermore, the study results indicate that to increase the satisfaction of existing customers; it should continue to be improved so that there is no decline by paying attention to service and other aspects such as location, so this can achieve.